Micro silica bead scintillators for the relative dosimetry of a stereotactic radiosurgery unit - Chris J. Stepanek; Jack D. Aylward; Ronald Hartley-Davies; Lucy Winch (Physics and Imaging in Radiation Oncology)
This work describes the procedure of using Micro Silica Beads (MSBs) to verify the output factors and profiles of a stereotactic radiosurgery unit. MSBs have shown acceptable dosimetric accuracy for measurement of Detector Output Ratios (DORs) and shot profiles, down to a full width at half maximum (FWHM) of 5 mm. DORs measured with MSBs were within 1.5 % of radiochromic film, and 3 % of a microdiamond detector. Measured FWHM were within 0.2 mm of planning system and radiochromic film. MSBs can be used as an effective substitute to radiochromic film for measurement of shot profiles and DORs.